Composite adsorbent, adsorption column, silane filtration system and filtration method
By using composite adsorbents, combined with the synergistic effects of activated carbon, UiO-66, cationic exchange resin and other components, the problem of insufficient adsorption capacity of traditional single adsorbents in silane purification is solved, and efficient purification of silanes and industrial applications are achieved.
Patent Information
- Application Number
- CN202510019551.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-07
AI Technical Summary
Traditional single adsorbents have insufficient adsorption capacity in silane purification and cannot meet the comprehensive needs of silane purification.
A composite adsorbent is used, which consists of particulate activated carbon, UiO-66, cationic exchange resin, alumina, nano zinc oxide and 3-aminopropyltriethoxysilicon modified ZSM-5 molecular sieve, and is highly efficient purification through synergistic effects between the components.
It realizes efficient purification of silanes, enhances adsorption performance, stability and applicability, and provides efficient and reliable technical solutions for the silane purification industry.
Smart Images

Figure CN119425648B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silane purification, in particular to a composite adsorbent, an adsorption column, a silane filtering system and a filtering method. Background Art
[0002] Silane is an important chemical raw material, widely used in the semiconductor, photovoltaic industry and the preparation of organosilicon compounds. However, due to its high chemical activity and low purity tolerance, silane has extremely stringent purity requirements during production, storage and application. Impurities in silane (such as moisture, oxides, organic matter and metal ions, etc.) will not only affect the performance of downstream products, but may also cause equipment corrosion, production failures and even safety hazards. Therefore, silane purification technology has become one of the key links in the development of silane-related industries.
[0003] At present, silane purification is mainly achieved through adsorption technology. Adsorption technology relies on the selective adsorption capacity of adsorbents for different impurities. By optimizing the material and process parameters of the adsorbent, the purity of silane can be significantly improved. However, common single adsorbents on the market, such as activated carbon, metal-organic frameworks (MOFs) or ion exchange resins, often have the following shortcomings:
[0004] 1. Limited adsorption range: A single adsorbent usually has a high selectivity for specific impurities, but insufficient adsorption capacity for other types of impurities, resulting in an inability to meet the comprehensive needs of silane purification.
[0005] 2. Low adsorption capacity: The adsorption capacity of some adsorbents is limited. They are prone to failure under conditions of high flow rate or long-term use and cannot meet the requirements of industrial continuous production.
[0006] 3. Insufficient thermal stability and mechanical strength: The performance of some adsorbents decreases under high temperature or high pressure environments, affecting their applicability in complex working conditions. Summary of the invention
[0007] In view of the above problems existing in the prior art, the present invention is proposed.
[0008] Therefore, the problem to be solved by the present invention is that the adsorption capacity of the traditional single adsorbent is insufficient.
[0009] In order to solve the above technical problems, in the first aspect, the present invention provides the following technical solutions: a composite adsorbent, calculated by mass fraction of raw materials, comprising:
[0010] 50-53 parts of granular activated carbon, 28-30 parts of UiO-66, 18-22 parts of cationic exchange resin, 5-15 parts of aluminum oxide, 1-10 parts of nano zinc oxide, and 1-10 parts of molecular sieve modified by silane coupling agent.
[0011] As a preferred embodiment of the composite adsorbent of the present invention, the cationic exchange resin is a sulfonic acid cationic resin, and the molecular sieve modified by the silane coupling agent is a ZSM-5 modified by 3-aminopropyltriethoxysilane.
[0012] In a second aspect, the present invention further provides an adsorption column, which comprises at least two V-shaped nets arranged along the axial direction of the tank body, with the tip of the V-shaped net facing the gas direction; both sides of the V-shaped net are filled with the above-mentioned composite adsorbent.
[0013] As a preferred solution of the adsorption column of the present invention, a jacket is provided inside the tank body for passing a heat exchange medium.
[0014] As a preferred solution of the adsorption column of the present invention, filter screens are respectively arranged at both ends of the tank body, and a discharge port and a replacement port are also arranged at the bottom of the tank body.
[0015] In a third aspect, the present invention also provides a silane purification filtration system, which comprises a first adsorption column group and a second adsorption column group connected in series; the first adsorption column group comprises at least two adsorption columns connected in parallel; the second adsorption column group comprises at least one adsorption column; the adsorption columns in the first adsorption column group and the second adsorption column group are both the above-mentioned adsorption columns.
[0016] As a preferred solution of the silane purification filtration system of the present invention, a heat exchanger is connected in series between the first adsorption column group and the second adsorption column group, and the heat exchanger is used for exchanging heat for the gas.
[0017] As a preferred solution of the silane purification filtration system of the present invention, the first adsorption column group and the second adsorption column group are further connected with an exhaust gas discharge pipeline for discharging exhaust gas.
[0018] As a preferred solution of the silane purification filtration system of the present invention, the filtered gas outlet pipeline is also connected to an analysis pipeline for analyzing the filtered gas.
[0019] As a preferred embodiment of the silane purification filtration system of the present invention, it further comprises a regeneration gas pipeline, which is respectively connected to the first adsorption column group and the second adsorption column group (500) and can be connected to the exhaust gas discharge pipeline.
[0020] In a fourth aspect, the present invention further provides a silane purification and filtering method, which comprises passing the silane gas to be purified into at least one closed space filled with the above-mentioned composite adsorbent for filtering.
[0021] As a preferred embodiment of the silane purification and filtration method of the present invention, the silane gas to be purified is passed into at least two parallel closed spaces for primary filtration; and the silane gas after the primary filtration is passed into at least one of the closed spaces again for secondary filtration.
[0022] As a preferred embodiment of the silane purification and filtration method of the present invention, it also includes that the silane gas after the secondary filtration is first tested and analyzed before being discharged into the subsequent system. If the analysis is qualified, it is no longer input into the closed space.
[0023] As a preferred embodiment of the silane purification and filtration method of the present invention, the filtration temperature of the silane gas is 20-28°C.
[0024] As a preferred embodiment of the silane purification and filtration method of the present invention, the pressure of the silane gas during filtration is 1 to 2 bar.
[0025] As a preferred embodiment of the silane purification and filtration method of the present invention, the gas flow rate of the silane gas during filtration is 0.5 to 2 L / min.
[0026] The beneficial effects of the present invention are as follows: the present invention designs a composite adsorbent for silane purification, and the composite adsorbent formula realizes efficient purification of silane through the synergistic effect between the components. Activated carbon, UiO-66, cationic exchange resin, alumina, nano zinc oxide and ZSM-5 together constitute an adsorption system with complementary functions and excellent performance, providing strong technical support for the purification of silane.
[0027] The composite adsorbent of the present invention is suitable for various silane purification systems, and the adsorption parameters can be flexibly adjusted according to different working conditions. It has a wide range of industrial application value, and overall embodies significant advantages in adsorption performance, stability and applicability. It provides an efficient and reliable technical solution for the silane purification industry, and has obvious technical advancement and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 Schematic diagram of the structure of the adsorption column.
[0030] Figure 2 Schematic diagram of the silane purification system. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below in conjunction with the accompanying drawings.
[0032] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0033] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor is it an embodiment that is mutually exclusive with other embodiments, either individually or selectively.
[0034] Unless otherwise specified, the raw materials used in the present invention are all commercially available in the art, including:
[0035] The specific surface area of granular activated carbon is ≥1500m 2 / g, dried at 100°C for 4 hours, and crushed to 30-100μm range after removing moisture to ensure uniform particles;
[0036] UiO-66(Zr) purity>95%, CAS#:1072413-89-8;
[0037] The particle size of sulfonic acid cationic resin is 0.35-1.2 mm, and the CAS number is 41678;
[0038] The 3-aminopropyltriethoxysilane-modified ZSM-5 was synthesized according to the literature "Synthesis of hierarchical pore structure ZSM-5 molecular sieves under the action of silane coupling agent and mesoporous template agent".
[0039] The specific experimental conditions for the performance test of the composite adsorbent of the present invention are:
[0040] (1) Gas conditions: simulated silane gas (SiH4, containing 2% water, 0.5% oxide, and 0.3% metal impurities).
[0041] (2) Main experimental equipment: adsorption column simulation device, high-precision gas chromatograph (GC), atomic absorption spectrometer (AAS), Karl Fischer moisture meter, etc.
[0042] (3) The test indicators are: water removal rate, VOC removal rate, metal ion removal rate, silane purity improvement, adsorption capacity and recovery rate.
[0043] Each group of experiments was repeated 3 times, and the average value was taken for analysis.
[0044] Example 1
[0045] This is the first embodiment of the present invention, which provides a composite adsorbent, specifically:
[0046] 1) Weigh the raw materials according to the following formula:
[0047] 52 parts of granular activated carbon, 30 parts of UiO-66, 20 parts of sulfonic acid cationic resin, 10 parts of alumina, 5 parts of nano zinc oxide, 5 parts of 3-aminopropyltriethoxysilane-modified ZSM-5;
[0048] 2) According to the ratio requirements of step 1), weigh the raw materials, pour all the materials into a V-type mixer or a high-efficiency stirrer, stir at 200 rpm for 15 minutes, spray 0.1 wt.% ethanol as a dispersant to avoid particle agglomeration, and place the mixed sample in an 80°C drying oven for 8 hours to remove moisture and ethanol to obtain a composite adsorbent.
[0049] Example 2
[0050] The difference between this embodiment and embodiment 1 is that the raw material formula is adjusted to:
[0051] 53 parts of granular activated carbon, 28 parts of UiO-66, 18 parts of sulfonic acid cationic resin, 15 parts of alumina, 1 part of nano zinc oxide, 10 parts of 3-aminopropyltriethoxysilane-modified ZSM-5;
[0052] The remaining steps and processes are all referred to Example 1 to obtain the composite adsorbent of this example.
[0053] Example 3
[0054] The difference between this embodiment and embodiment 1 is that the raw material formula is adjusted to:
[0055] 50 parts of granular activated carbon, 32 parts of UiO-66, 22 parts of sulfonic acid cationic resin, 5 parts of alumina, 10 parts of nano zinc oxide, 5 parts of 3-aminopropyltriethoxysilane-modified ZSM-5;
[0056] The remaining steps and processes are all referred to Example 1 to obtain the composite adsorbent of this example.
[0057] Comparative Example 1
[0058] Comparative Example 1 This comparative example differs from Example 1 in that UiO-66 is omitted and replaced with an equal amount of granular activated carbon, and the remaining steps and processes are referred to Example 1 to obtain the composite adsorbent of this comparative example.
[0059] Comparative Example 2
[0060] The difference between this comparative example and Example 1 is that the sulfonic acid cationic resin is omitted and replaced with an equal amount of granular activated carbon, and the remaining steps and processes are all referred to Example 1 to obtain the composite adsorbent of this comparative example.
[0061] Comparative Example 3
[0062] The difference between this comparative example and Example 1 is that alumina is omitted and replaced with an equal amount of granular activated carbon, and the remaining steps and processes are all referred to Example 1 to obtain the composite adsorbent of this comparative example.
[0063] Comparative Example 4
[0064] The difference between this comparative example and Example 1 is that nano zinc oxide is omitted and replaced with an equal amount of granular activated carbon, and the remaining steps and processes are all referred to Example 1 to obtain the composite adsorbent of this comparative example.
[0065] Comparative Example 5
[0066] The difference between this comparative example and Example 1 is that the 3-aminopropyltriethoxysilicon-modified ZSM-5 is omitted and replaced with an equal amount of granular activated carbon, and the remaining steps and processes are referred to Example 1 to obtain the composite adsorbent of this comparative example.
[0067] The relevant properties of the composite adsorbents of Examples 1 to 3 and Comparative Examples 1 to 5 were tested, and the comparison results are shown in Table 1.
[0068] Table 1
[0069]
[0070]
[0071] As can be seen from Table 1, the adsorbent formula designed by the present invention achieves efficient purification of silane through the synergistic effect of various components, wherein the granular activated carbon, as the basic component of the composite adsorbent, can capture and remove a large amount of impurities in silane with its porous structure and excellent adsorption capacity, and provides a good platform for the synergistic effect of other components;
[0072] As a high-performance metal-organic framework material, UiO-66 has excellent specific surface area, pore size control ability and chemical stability. In the composite adsorbent, UiO-66 can further expand the adsorption range, especially for some impurities that are difficult to be adsorbed by activated carbon. At the same time, the pore structure of UiO-66 helps to screen and separate molecules of different sizes, thereby improving the selectivity of purified silane.
[0073] Cationic exchange resins adsorb metal ions in silane through an ion exchange mechanism, effectively reducing the content of these impurities. In addition, the addition of resins also enhances the regeneration performance of the adsorbent and extends its service life. Alumina, with its high stability and chemical inertness, plays a role in stabilizing the skeleton in the composite adsorbent.
[0074] Alumina can not only improve the mechanical strength of the adsorbent to prevent it from breaking due to force during the purification process, but also form hydrogen bonds and other interactions with silane molecules through its surface functional groups such as hydroxyl groups, thereby enhancing the adsorption effect;
[0075] Nano zinc oxide, with its unique nanostructure and excellent catalytic performance, brings more active sites and catalytic pathways to the composite adsorbent. It can react chemically with silane molecules during the adsorption process, thereby accelerating the purification process and improving the purification efficiency;
[0076] 3-aminopropyltriethoxysilane modified ZSM-5 molecular sieve provides additional screening and adsorption capacity for composite adsorbents with its special pore structure and surface properties. It can not only screen according to molecular size and shape, but also interact with silane molecules through its surface amino functional groups, thereby further improving the purification effect.
[0077] Example 4
[0078] This example is used to explore the effect of different types of metal organic frameworks on the performance of the prepared composite adsorbent. Specifically, the difference from Example 1 is that the UiO-66 in the raw material formula is adjusted to ZIF-8, MOF-801, and MOF-74, respectively. The remaining steps and processes are all referred to Example 1 to obtain the composite adsorbent of this example. The relevant properties thereof are tested and compared with those of Example 1. The results are shown in Table 2.
[0079] Table 2
[0080]
[0081] As can be seen from Table 2, different types of metal organic frameworks have a certain influence on the comprehensive performance of the prepared composite adsorbent. UiO-66, as an organic metal framework material, has the characteristics of large specific surface area, high porosity, and excellent chemical stability, mechanical stability and thermal stability. In the purification of silane. The pore structure of UiO-66 can effectively capture and separate silane molecules, and its chemical stability ensures that no adverse chemical reactions occur with silane or other impurities during the adsorption process. Specifically:
[0082] The combination of UiO-66 and granular activated carbon can form a complementary pore structure, thereby improving the adsorption efficiency of silane molecules and impurities. The chemical stability of UiO-66 helps to maintain the overall stability of the composite adsorbent and prevent performance degradation caused by chemical reactions during the adsorption process. The pore structure of UiO-66 can serve as a support for sulfonic acid cationic resins, increasing their adsorption surface area, thereby improving the ability of ion exchange and acid-base regulation. The interaction between UiO-66 and sulfonic acid cationic resins helps to form a more stable adsorption environment and improve the purification efficiency of silane.
[0083] The pore structure of UiO-66 can accommodate nanoparticles of alumina and nano-zinc oxide to form a more complex adsorption system, thereby promoting the catalytic conversion and further purification of silane molecules. The interaction between UiO-66 and 3-aminopropyltriethoxysilane-modified ZSM-5 can also enhance the recognition and capture ability of silane molecules.
[0084] In contrast, although ZIF-8, MOF-801 and MOF-74 are also metal organic framework materials, their pore structure, chemical stability and interaction with other components are significantly different from UiO-66. These differences lead to their performance in composite adsorbents being inferior to that of UiO-66.
[0085] Example 5
[0086] This example is used to explore the effect of the amount of different metal organic frameworks on the performance of the prepared composite adsorbent. Specifically, the difference from Example 1 is that the metal organic frameworks in the raw material formula are adjusted to 22, 26, 34, and 38 parts, respectively, and the remaining steps and processes are all referred to Example 1 to obtain the composite adsorbent of this example. The relevant properties are tested and compared with Example 1 (30 parts). The results are shown in Table 3.
[0087] Table 3
[0088]
[0089] It can be seen from Table 3 that the dosage of different metal organic frameworks has a certain influence on the performance of the prepared composite adsorbent. As mentioned above, UiO-66 plays a key role in the preparation of the composite adsorbent. It interacts with other components in the system. When the content of UiO-66 changes, this synergistic effect will be destroyed, thereby affecting the overall performance of the composite adsorbent.
[0090] Example 6
[0091] This example is used to explore the effect of different types of molecular sieves on the performance of the prepared composite adsorbent. The difference from Example 1 is that the 3-aminopropyltriethoxysilicon-modified ZSM-5 in the raw material formula is adjusted to be unmodified ZSM-5 molecular sieve, XH-9 molecular sieve, and 4A molecular sieve, respectively. The remaining steps and processes are all referred to Example 1 to obtain the composite adsorbent of this example. Its relevant properties are tested and compared with those of Example 1. The results are shown in Table 4.
[0092] Table 4
[0093]
[0094] As can be seen from Table 4, 3-aminopropyltriethoxysilane-modified ZSM-5 plays an irreplaceable role in the composite adsorbent. ZSM-5 is modified by silanization to introduce specific functional groups, thus giving it unique properties. Although unmodified ZSM-5 also has a certain adsorption capacity, its hydrophobicity is weaker and the adsorption sites are fewer than those of modified ZSM-5, so the overall performance is reduced. Although XH-9 molecular sieve has a unique pore structure and a certain adsorption capacity, it is incompatible or has weak interactions with other components in the composite adsorbent, resulting in a decrease in overall performance; 4A molecular sieve is mainly used to remove small molecular impurities and moisture, but when dealing with silane gas, its adsorption capacity and selectivity may not be as good as those of modified ZSM-5.
[0095] Example 7
[0096] This example is used to explore the effect of the amount of different molecular sieves on the performance of the prepared composite adsorbent. The difference from Example 1 is that the amount of 3-aminopropyltriethoxysilane-modified ZSM-5 in the raw material formula is adjusted to 1, 7, and 12 parts, respectively. The remaining steps and processes are all based on Example 1 to obtain the composite adsorbent of this example. The relevant properties are tested and compared with Example 1 (5 parts). The results are shown in Table 5.
[0097] Table 5
[0098]
[0099] As can be seen from Table 5, adjusting the amount of molecular sieve has a significant effect on the performance of the prepared adsorbent. When the amount of modified ZSM-5 is reduced, the adsorption sites and functional characteristics it provides are greatly reduced, resulting in the composite adsorbent's ability to remove moisture, VOCs, and metal ions being weakened, the purity of silane gas is reduced, the adsorption capacity is reduced, and the recovery rate may also be reduced due to low adsorption efficiency. Excessive use of modified ZSM-5 may cause the pore structure in the composite adsorbent to be overfilled, reducing the effective adsorption space. At the same time, too much modified ZSM-5 may interact adversely with other components, affecting adsorption efficiency and selectivity.
[0100] In summary, the composite adsorbent for silane purification provided by the present invention realizes efficient purification of silane through the synergistic effect of the components. Activated carbon, UiO-66, cationic exchange resin, alumina, nano zinc oxide and ZSM-5 together constitute an adsorption system with complementary functions and excellent performance, and each of them is indispensable. Under the appropriate ratio, it provides strong technical support for the purification of silane.
[0101] Example 8
[0102] This embodiment provides an adsorption column, which is filled with the composite adsorbent as described in Embodiment 1. The adsorption column includes a tank body 100 and a V-shaped net 200.
[0103] Specifically, refer to Figure 1 The V-shaped net 200 is a Johnson net, and multiple V-shaped nets are arranged at intervals along the axial direction of the tank body 100. The tip of the V-shaped net 200 faces the direction of the gas. That is, when the adsorption column is bottom-in and top-out, the tip of the V-shaped net 200 faces downward. The top of the V-shaped net 200 is also evenly provided with 14 / 16 / 20 small holes. The composite adsorbent is filled between the V-shaped nets 200.
[0104] A jacket is also arranged around the inside of the tank 100, and circulating water, seven-degree water or other cooling medium or heating medium can be passed into the jacket, which can well provide or remove the temperature inside the adsorption column. Such a design can be used to well control the temperature inside the adsorption column, ensuring that the adsorption process is carried out under suitable adsorption stability inside the adsorption column to ensure the adsorption effect.
[0105] The upper and lower ends of the jacket are also provided with a heat exchange medium inlet and a heat exchange medium outlet, so as to facilitate the replacement of the heat exchange medium. Filters are installed at the top and bottom of the tank body 100, and a discharge port and a replacement port are provided at the bottom of the tank body 100.
[0106] Example 9
[0107] The present embodiment provides a silane purification filtration system, which includes a first adsorption column group 400 and a second adsorption column group 500 connected in series.
[0108] Specifically, refer to Figure 2 The first adsorption column group 400 includes at least two adsorption columns connected in parallel. A plurality of adsorption columns may be connected in parallel. In this embodiment, two adsorption columns are connected in parallel. The adsorption columns are the adsorption columns described in Embodiment 8.
[0109] The second adsorption column group 500 includes at least one adsorption column. The adsorption columns in the second adsorption column group 500 may be multiple adsorption columns connected in series. In the present embodiment, the number of adsorption columns in the second adsorption column group is one.
[0110] Preferably, a heat exchanger 600 is connected in series between the first adsorption column group 400 and the second adsorption column group 500. The heat exchanger 600 is used to heat the gas.
[0111] Each adsorption column in the first adsorption column group 400 and the second adsorption column group 500 is connected to a waste gas discharge pipeline, and the regeneration gas and waste gas under maintenance can be discharged from the pipeline.
[0112] The gas outlet pipeline is also connected to an analysis pipeline, and a switch valve is used for remote control. Qualified products that have passed the analysis are sent from the outlet pipeline to the subsequent system.
[0113] The regeneration gas pipeline is communicated with the first adsorption column group 400 and the second adsorption column group 500 respectively and can be communicated with the exhaust gas discharge pipeline.
[0114] In this embodiment, among the three adsorption columns, the first two are connected in parallel and then connected in series with the last one. The advantages of this arrangement are:
[0115] 1. The parallel structure allows the silane gas to be distributed between the two adsorption columns, thereby increasing the processing capacity of the system. The amount of gas processed by each adsorption column is reduced, which helps to improve the efficiency of a single adsorption column.
[0116] 2. As the gas is split between the two adsorption columns, the flow rate in each column is reduced, resulting in a reduction in pressure drop, which can reduce the energy consumption of the pump and extend the service life of the adsorbent.
[0117] 3. If one adsorption column fails, the other adsorption column can still continue to work, ensuring the continuous operation of the system without causing the entire system to shut down.
[0118] 4. In parallel configuration, a single adsorption column can be maintained or replaced without interrupting the entire system.
[0119] 5. After the initial purification in the parallel adsorption columns, the series adsorption columns can be used as a deep purification stage to capture any residual impurities that were not removed in the previous stage.
[0120] 6. Adsorption columns connected in series can be optimized for specific types of impurities, further improving the purification efficiency of the overall system.
[0121] The traditional method of directly connecting three adsorption columns in series will lead to over-processing, increase unnecessary costs and energy consumption, while the method of connecting in parallel first and then in series can achieve deep purification while ensuring the processing speed. Connecting three adsorption columns in series will accelerate the adsorbent saturation rate of the first two columns, while the third column may not be fully utilized. The method of connecting in parallel and then in series can more evenly utilize the adsorption capacity of each adsorption column.
[0122] Compared with directly connecting three adsorption columns in parallel, although connecting three adsorption columns in parallel can handle a larger flow rate, if there is no deep purification step in series, some difficult-to-remove impurities will penetrate all parallel adsorption columns. Connecting three adsorption columns in parallel will be risky when dealing with certain high-concentration impurities, and the design of connecting in parallel first and then in series provides an extra layer of safety.
[0123] Example 10
[0124] This embodiment provides a silane purification and filtering method, which includes passing the silane gas to be purified into a closed space filled with the gas described in Embodiment 1 for filtering.
[0125] The enclosed space can be a space with an inlet and an outlet such as a tank or a box. In this embodiment, the adsorption column described in Embodiment 7 can be directly used. Two adsorption columns can be connected in parallel first, and then one adsorption column is connected in series with the first two.
[0126] During filtration, the gas to be purified is first passed through two parallel adsorption columns for primary filtration, and then the silane gas after the primary filtration is passed through the next adsorption column for secondary filtration. The silane gas after the secondary filtration is tested, and if qualified, it is discharged to the subsequent system.
[0127] Preferably, the filtering temperature of the silane gas is 20-28° C., the pressure is 1-2 bar, and the gas flow rate is 0.5-2 L / min.
[0128] In summary, the composite adsorbent of the present invention is suitable for various silane purification systems, and the adsorption parameters can be flexibly adjusted according to different working conditions. It has a wide range of industrial application value and overall reflects significant advantages in adsorption performance, stability and applicability. It provides an efficient and reliable technical solution for the silane purification industry and has obvious technological advancement and practical value.
[0129] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A silane purification filtration system, characterized in that: A first adsorption column group (400) and a second adsorption column group (500) connected in series with each other; The first adsorption column group (400) comprises at least two adsorption columns connected in parallel; The second adsorption column group (500) comprises at least one adsorption column; The adsorption columns in the first adsorption column group (400) and the second adsorption column group (500) comprise at least two V-shaped nets (200) arranged axially along the tank body (100), with the tips of the V-shaped nets (200) facing the direction of the gas; Both sides of the V-shaped net (200) are filled with a composite adsorbent, and the composite adsorbent, calculated in terms of mass fraction of the raw material, comprises: 50-53 parts of granular activated carbon, 28-30 parts of UiO-66, 18-22 parts of sulfonic acid cationic resin, 5-15 parts of alumina, 1-10 parts of nano zinc oxide, 1-10 parts of 3-aminopropyltriethoxysilane-modified ZSM-5; The tank body (100) is provided with a jacket inside for passing a heat exchange medium; Filter screens (300) are respectively arranged at both ends of the tank body (100), and a discharge port and a replacement port are also arranged at the bottom of the tank body (100).
2. The silane purification filtration system according to claim 1, characterized in that: A heat exchanger (600) is connected in series between the first adsorption column group (400) and the second adsorption column group (500), and the heat exchanger (600) is used to perform heat exchange on the gas.
3. The silane purification filtration system according to any one of claims 1 or 2, characterized in that: The first adsorption column group (400) and the second adsorption column group (500) are also connected to an exhaust gas discharge pipeline for discharging exhaust gas.
4. The silane purification filtration system according to claim 3, characterized in that: The filtered gas outlet pipeline is also connected with an analysis pipeline for analyzing the filtered gas.
5. The silane purification filtration system according to claim 4, characterized in that: It also includes a regeneration gas pipeline, which is communicated with the first adsorption column group (400) and the second adsorption column group (500) respectively and can be communicated with the exhaust gas discharge pipeline.
6. A silane purification and filtration method, characterized in that: Using the silane purification filtration system according to claim 1, The silane gas to be purified is passed into at least one closed space filled with the composite adsorbent for filtration.
7. The silane purification and filtration method according to claim 6, characterized in that: Passing the silane gas to be purified into at least two of the enclosed spaces connected in parallel to perform a primary filtration; The silane gas after the primary filtration is introduced into at least one of the enclosed spaces again for secondary filtration.
8. The silane purification and filtration method according to claim 7, characterized in that: It also includes that the silane gas after the secondary filtration is first tested and analyzed before being discharged into the subsequent system. If the analysis is qualified, it is no longer input into the confined space.
9. The silane purification and filtration method according to claim 8, characterized in that: The filtering temperature of the silane gas is 20-28°C.
10. The silane purification and filtration method according to claim 9, characterized in that: The pressure of the silane gas during filtration is 1-2 bar.
11. The silane purification and filtration method according to any one of claims 6 to 10, characterized in that: The gas flow rate of the silane gas during filtration is 0.5~2L / min.
Citation Information
Patent Citations
Preparation method of ceramic matrix composite used for methane sensor
CN105948818A
Active carbon embedded MOF adsorption material as well as preparation method and application thereof
CN113908809A
An Absorbent with Zeolite for Deodorization
KR1020040102615A
Composite-type multi-layered Chemical Filter and preparation method thereof
KR1020230062025A